An intervention to improve the quality of medication abortion knowledge among pharmacists in India. Issue 3 (19th September 2019) - Diamond‐Smith, Nadia; Phillips, Beth; Percher, Joanna; Saxena, Malvika; Dwivedi, Pravesh; Srivastava, Aradhana
Abstract: Objective: To test an infographic two‐pager on medication abortions (MA) aimed to improve pharmacists counseling in India. Methods: A quantitative baseline survey was conducted among 283 pharmacists in three districts around Lucknow, Uttar Pradesh in January 2018. The intervention (infographic) was given to 117 of these pharmacists a few weeks later and a follow‐up survey was conducted 3 months later with 281 pharmacists. In addition, mystery clients were sent to 115 of the pharmacists. Results: A statistically significant improvement in knowledge post‐intervention was found, compared to pre‐, for almost all quality items measured. Difference‐in‐difference estimators showed a difference in knowledge among indicators related to misoprostol in particular. However, mystery client reports showed few differences in pharmacist behaviors between intervention and control pharmacists. Conclusion: This simple, paper‐based intervention, which required no training, showed a significant improvement in pharmacists' knowledge and was welcomed by the providers. Translating knowledge into behavior change, however, seems more difficult to impact. Adapting this simple intervention to motivate providers to change behaviors could improve the quality of care provided by pharmacists in India. Abstract : A simple infographic improved pharmacists' knowledge about appropriate medication abortion counseling but did not change behaviors.